Intrauterine Therapy - Gottschalk, Ingo; Weber, Eva Christin; Bedei, Ivonne; Axt-Fliedner, Roland; Strizek, Brigitte; Berg, Christoph (Ultraschall in der Medizin - European Journal of Ultrasound, 2025)
Since the first intrauterine interventions were carried out in the 1970 s under what today would be considered basic conditions, the range of prenatal interventions has steadily expanded, as has the frequency with which these interventions are carried out at specialized centers. Although most of these procedures are minimally invasive, they are invariably associated with considerable risks for the fetus and, depending on the surgical method, also for the expectant mother. For this reason, most centers worldwide limit themselves to interventions for fetal diseases which, if untreated, have a fatal course or experience a significant deterioration in the postnatal prognosis during the course of intrauterine development. This is all the more significant as only a small proportion of prenatal interventions have been successfully investigated in controlled clinical trials. The only exceptions are laser therapy for feto-fetal transfusion syndrome, intrauterine closure of spina bifida, and tracheal occlusion for diaphragmatic hernia with severe pulmonary hypoplasia. This article is intended to provide an overview of the fetal conditions that are candidates for intrauterine therapy and of the evidence for the individual interventions.Seitdem in den 70er-Jahren des letzten Jahrhunderts die ersten intrauterinen Eingriffe unter aus heutiger Sicht sehr einfachen Rahmenbedingungen durchgeführt wurden, hat sich das Spektrum der vorgeburtlichen Eingriffe stetig erweitert – und auch die Frequenz, mit der diese Eingriffe an spezialisierten Zentren durchgeführt werden. Zwar erfolgen die meisten dieser Eingriffe minimalinvasiv, dennoch sind sie ausnahmslos mit erheblichen Risiken für den Fetus und, in Abhängigkeit von der Operationsmethode, auch für die werdende Mutter verbunden. Daher beschränken sich die meisten Zentren weltweit auf Interventionen bei fetalen Erkrankungen, die unbehandelt einen tödlichen Verlauf haben oder im Laufe der intrauterinen Entwicklung eine deutliche Verschlechterung der postnatalen Prognose erfahren. Dies ist umso bedeutender, als nur ein kleiner Teil der vorgeburtlichen Eingriffe erfolgreich im Rahmen kontrollierter klinischer Studien untersucht wurde. Ausnahmen sind lediglich die Lasertherapie des fetofetalen Transfusionssyndroms, der intrauterine Verschluss der Spina bifida und die Trachealokklusion bei Zwerchfell-Hernien mit schwerer pulmonaler Hypoplasie. Dieser Artikel soll einen Überblick über diejenigen fetalen Erkrankungen geben, die Kandidaten für eine intrauterine Therapie sind, sowie über die Evidenz der einzelnen Eingriffe.
Keywords: twin to twin transfusion syndrome; congenital diaphragmatic hernia; intrauterine valvuloplasty; meningomyelocele; fetal intervention